A Systematic Review and Meta-analysis of Free-style Flaps: Risk Analysis of Complications. Issue 2 (February 2018) - Qian, Youlei; Li, Guangxue; Zang, Huiran; Cao, Saisai; Liu, Yan; Yang, Kai; Mu, Lan
Abstract : Background: Free-style flaps allow surgeons to overcome anatomical variations and raise perforator flaps wherever a pulsatile signal can be detected. We performed a systematic review and meta-analysis to identify the risk factors for complications and indications for free-style flaps in soft-tissue defect reconstructions. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. The databases of MEDLINE, PubMed, ScienceDirect, and Cochrane Library were searched from January 1991 to January 2017 for original articles describing free-style flaps in soft-tissue defect reconstruction. Results: A total of 17 articles met the inclusion criteria, representing 453 free-style flaps. The percentage of free-style flaps conducted after primary oncologic resection was 54.4% (246/453). Free-style flaps were mostly used in the head and neck region (35.5%), and most of them were designed as pedicled perforator flaps (96.7%). Complete flap survival was accomplished in 91.8% of the free-style flaps. Complications were found in 13.5% of cases, and 2 risk factors were identified: extremity defects (risk ratio, 2.39; P = 0.006) and single perforator flaps (risk ratio, 4.93; P = 0.002). No significant differences were found among the criteria including patients aged greater than 60 years, female gender, chronic etiology, flap size over 100 cm 2, flap rotation, or perforator skeletonization. Conclusions: Free-style flaps are both reliable and advanced forms of perforator flaps for use in soft-tissue defect reconstructions. Defects located on the extremities and flaps with single perforators are risk factors for flap failure and complications.